Liquidity management of US global banks: Internal capital markets in the great recession - Nicola Cetorelli; Linda Goldberg (Federal Reserve Bank of New York, 2011)
The recent crisis highlighted the importance of globally active banks in linking markets. One channel for this linkage is the liquidity management of these banks, specifically the regular flow of funds between parent banks and their affiliates in diverse foreign markets. We use the Great Recession as an opportunity to identify the balance-sheet shocks to parent banks in the United States and then explore which features of foreign affiliates are associated with protecting, for example, their status as important locations in sourcing funding or as destinations for foreign investment activity. We show that distance from the parent organization plays a significant role in this allocation, where distance is bankaffiliate specific and depends on the location's ex ante relative importance in local funding pools and overall foreign investment strategies. These flows are a form of global interdependence previously unexplored in the literature on international shock transmission.
Keywords: E44; F36; G32; 330; bank; global; liquidity; transmission; capital markets; crisis; contagion; Internationaler Finanzmarkt; Internationale Bank; Globalisierung; Bankenliquidität; Management; Finanzmarktkrise; Ansteckungseffekt; USA; Welt